Clan and tribal perspectives on social, economic and environmental sustainability : indigenous stories from around the globe - Spee, James C. (Emerald Publishing Limited, 2021)
From the Indigenous perspective, sustainability must be understood as a means of survival. In a climate of in-migration, clan and tribal communities have been forced to build sustainable solutions together to protect their sovereignty, recognition and mutual respect. In the midst of a global pandemic that threatens the economic and social well-being of millions of people, this edited collection addresses the social, economic, and environmental sustainability of tribes, clans, and Indigenous cultures across national and global origins. Acknowledging that these peoples around the globe have addressed threats to their survival for millennia, the authors showcase examples of indigenous groups spanning South Africa, Nigeria, Australia, New Zealand, Pakistan, Afghanistan, Bolivia and North America. Regional examples also come from Rwanda, Cameroon, Congo, Ethiopia, East Timor, Papua New Guinea, the Andaman and Nicobar Islands, Easter Island, and Nunavit, Canada. Breaking fresh ground by shining a light on sustainability journeys from outside the global mainstream, this book demonstrates how sustainable recovery and development occurs in respectful collaboration between equals.